Chemical Composition, Micorencapsulation and Comparative Antimicrobial Studies of Unencapsulated and Encapsulated Carrot Seed Essention Oil. Issue 1 (2nd January 2023) - Singh, Amrinder; Bhardwaj, Urvashi; Kaur, Ramandeep; Vyas, Pratibha
Abstract: The present study aimed to isolate and encapsulate carrot seed essential oil (CSEO) and to compare the antimicrobial potential of unencapsulated and encapsulated essential oil. Hydrodistilled CSEO was colourless to yellowish in colour with yield of 1.6% w/w. Chemical characterization by GC/MS revealed Carotol, Daucol and Daucene as major components. Microencapsulation was carried out employing a complex coacervation technique. The influence of gelatin and carrot seed essential oil concentration on the various parameters such as size, morphology, thermal properties, encapsulation and loading efficiency of the microcapsules were investigated. Scanning electron microscopy displayed quasi-spherical microcapsules. The pyrolysis behavior under thermal properties was divided into three stages. The highest encapsulation efficiency was achieved with 4: 6 ratio of gelatin: CSEO. The encapsulated and unencapsulated CSEO showed moderate bactericidal activity against Staphylococcus aureus whereas minimal action against Escherichia coli . This study suggested the potential utilization of encapsulated essential oil for the long preservation of food stuff.